Gifted hands [videorecording (DVD)] : the Ben Carson story - Carter, Thomas, 1953-; Gooding, Cuba, Jr., 1968-; Elise, Kimberly, 1971-; Coden, Ron; Ellis, Aunjanue; Hoffman, Gus; Carson, Ben (Sony Pictures Home Entertainment, 2009)
Follows the life of Dr. Benjamin S. Carson, who overcame problems in school and obstacles in life to become a world-renowned neurosurgeon. His lifelong journey led him to become director of pediatric neurosurgery at Johns Hopkins Children's Center, a bestselling author, and a recipient of the Presidential Medal of Freedom. Includes behind-the-scenes, and featurettes.